Report of the Working Group on Nutrition Policy and Programme for the 4th Plan - Planning Commission (Planning Commission Government of India, 1968)
The Report of the Working Group on Nutrition Policy and Programmes for India’s Fourth Five-Year Plan (1970–1975) addresses the historical neglect of nutrition in national development and emphasizes its critical role in health, productivity, and social welfare. The report highlights widespread malnutrition, particularly among infants, pregnant, and nursing women, with deficiencies in protein, iron, and essential vitamins. It recommends an integrated nutrition strategy encompassing research, education, production of affordable nutritious foods, structured feeding programmes for children, and targeted community outreach, especially involving women’s organizations. Enhanced government-industry collaboration is proposed to scale production and standardize nutritional products. Financial allocations for key programmes, such as anemia prophylaxis and the Applied Nutrition Programme, are detailed, though funding gaps remain significant. The report calls for systematic, multi-dimensional interventions, including increased investment, cross-departmental coordination, and continuous monitoring, to effectively combat malnutrition and embed nutrition as a core component of India’s development agenda.
India Planning Commission
Keywords: Nutrition Policy; Malnutrition; Feeding Programmes; Nutritious Foods; Public Health; Community Involvement; Government-Industry Collaboration; Educational Initiatives; Nutritional Deficiencies; Applied Nutrition Programme; Fourth Five-Year Plan; Resource Allocation